Irish late Iron Age equestrian equipment in its insular and continental context - Maguire, Rena (Queen's University Belfast Irish archaeological monograph, 2021)
This is the first practical archaeological study of Irish Iron Age lorinery. The horse and associated equipment were very much at the heart of the social changes set in motion by contact with the Roman Empire; the examination of the snaffles and bosals allows us to bring the people of the Late Iron Age in Ireland into focus.